2014
DOI: 10.3389/fimmu.2014.00046
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells as Immunotherapy

Abstract: Regulatory T cells (Tregs) suppress exuberant immune system activation and promote immunologic tolerance. Because Tregs modulate both innate and adaptive immunity, the biomedical community has developed an intense interest in using Tregs for immunotherapy. Conditions that require clinical tolerance to improve outcomes – autoimmune disease, solid organ transplantation, and hematopoietic stem cell transplantation – may benefit from Treg immunotherapy. Investigators have designed ex vivo strategies to isolate, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 147 publications
1
108
0
3
Order By: Relevance
“…SLAMF3 stimulation could be beneficial in patients who exhibit resistance to IL-2 therapy or who cannot tolerate recombinant IL-2 treatment. Similarly, engagement of SLAMF3 could offer significant adjuvant therapeutic value to clinical trials in which in vitro expanded Tregs are transfused to patients with SLE, diabetes, and GVHD (44).…”
Section: Discussionmentioning
confidence: 99%
“…SLAMF3 stimulation could be beneficial in patients who exhibit resistance to IL-2 therapy or who cannot tolerate recombinant IL-2 treatment. Similarly, engagement of SLAMF3 could offer significant adjuvant therapeutic value to clinical trials in which in vitro expanded Tregs are transfused to patients with SLE, diabetes, and GVHD (44).…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge that Tregs can suppress immune responses against autoantigens and alloantigens has prompted exploration of Tregbased tolerogenic therapies for treatment of autoimmune disorders, organ transplant rejection, and graft-versus-host disease (GVHD) (4)(5)(6). Indeed, animal model studies have shown that adoptive Treg transfer is an effective strategy for suppressing immune-mediated diseases and immunologic complications of transplantation (7)(8)(9)(10).…”
Section: Cd4mentioning
confidence: 99%
“…Subpopulations of regulatory T cells (Tregs), which promote or inhibit the immune response, display yin-yang characteristics under certain conditions (35). The depletion of Tregs leads to the lack of suppression of immune cells, causing an excessive immune response and autoimmunity and promoting anti-tumor responses, while the expansion of Tregs can counteract autoimmunity and inhibit anti-tumor responses (36).…”
Section: T Cells and B Cellsmentioning
confidence: 99%